Family Support for Short-Status Pregnant Women to Prevent Gestational Stunting : Phenomenological Studies - Zuriati Muhamad; St. Surya Indah Nurdin; Asnidar Asnidar; Ilyas Abbas Ilyas Abbas; Dwi Nur Octaviani Katili (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: Maternal short stature with a height < 150 cm are at risk of giving birth to short babies (body length < 48 cm) Then, so that they become small and small children. The purpose of this study was to analyze family support for short pregnant women in dealing with their pregnancies. Methods: This study uses a qualitative research design with a phenomenological approach. The informants in this study were 12 short pregnant women and 9 village midwives. Data collection was carried out through in-depth interviews. The data were analyzed using the Interpretation of Phenomenology Analysis (IFA). Results: It is suggested that family support needs to be increased through the participation of community leaders and religious leaders, so that pregnant women can carry out their pregnancies happily and have support from those closest to them and have an impact on the health of the fetus. Conclusion: Family support needs to be increased through the participation of community leaders and religious leaders, so that pregnant women can carry out their pregnancies happily and have support from those closest to them and have an impact on the health of the fetus